Employment policies from a gender equality perspective in Mediterranean Europe developments and challenges - Ferreira V. (Women status in the Mediterranean: their rights and sustainable development, 2009)
Gender equality is a priority of the European Employment Strategy but, according to key indicators, only two European Mediterranean Countries have so far reached Lisbon target for female employment. Some indicators are presented to understand the complexity of the employment frame in EU Mediterranean Countries as the employment average in general, the education level, the fertility rate and the segregation rate. Many measures have been adopted by the European Commission to support the inclusion of women in the labour market such as: the implementation of children care services, family services, the reduction of pay gap (COM/2007/424) and the application of flexicurity principle (2007/359, promoting equal access to qualified employment entails measures to reconcile work and private life). The Roadmap for Equality between Women and Men was launched by the European Commission in 2006, but EU Mediterranean Countries adopted individual policies often resulting from a cultural model, still marked by the male family provider. The concept of flexicurity, in the wake of North European Countries, will change the structure of societies and allow sharing roles between the sexes inside and outside the families.
International Meeting on Women Status in the Mediterranean: their Rights and Sustainable Development, 2008/06/16-17, Bari (Italy)